The Influence of Employee Performance on the Quality of Administrative Services at the South Sulawesi Regional Settlement Infrastructure Center Officer - Hasriani Anriani; Sirajuddin Saleh; Jamaluddin Jamaluddin; Andi Nuzul Akbar (Journal of Social Science and Economics (JOSSE), 2025)
Employee performance plays a crucial role in enhancing the effectiveness of administrative services and in achieving organizational objectives. Consequently, this study holds significant importance in identifying the characteristics that influence service quality. The primary objective of this research is to examine the impact of employee performance on the quality of administrative services at the Housing Infrastructure Office in the South Sulawesi region. This study employs a descriptive design with a quantitative research approach. The sample consists of 67 employees working at the South Sulawesi Regional Settlement Infrastructure Office. Data were collected through observations, questionnaires, and documentation techniques. The collected data were analyzed using descriptive and inferential statistical methods. The results reveal that the performance level of employees at the South Sulawesi Regional Settlement Infrastructure Office remains below the expected standard. However, people generally perceive the office's administrative services to be of very high quality. Further analysis indicates that employee performance accounts for 65.1% of the variation in administrative service quality, while the remaining 34.9% can be attributed to other unidentified factors. Overall, the study demonstrates a strong and significant correlation between employee performance and the quality of administrative services at the Housing Infrastructure Office in the South Sulawesi region.